Studi Kelayakan Pembangkit Listrik Tenaga Surya di Taman Kampus II Universitas Pamulang Menggunakan PV-Syst - Muhammad Nur Iman; Seflahir Dinata (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Indonesia is currently very dependent on fossil energy, the availability of which is limited and has an emission effect on the environment. To sustain the availability of electrical energy, alternative energy sources are needed in the form of renewable energy, one of which is the Solar Power Plant (PLTS). This research discusses the design of an On Grid PLTS system in the park at Campus II, Pamulang University using Pvsyst 7.2 software by taking into account technical and economic aspects in three scenarios. In scenario 1, the On Grid PLTS is designed to suit the energy needs of the Pamulang University Campus II park, while in scenario 2 it uses an OFF Grid system and in scenario 3 it uses a Hybrid PLTS system (PLN+Batteries). Economic aspects are calculated using the Net Present Value (NPV) and Discounted Payback Period (DPP) methods. Technically, the Performance Ratio obtained was 83.59% and 83.53% respectively with Solar Fraction of 62.64% and 70.15% respectively. Economically, the NPV value obtained is positive and the investment return period is 7.78 years and 7.8 years respectively. So, designing an On Grid PLTS in the park of Pamulang University's Campus II is considered feasible.